New Records of Social Wasps (Hymenoptera: Vespidae, Polistinae) in Amazonas State, Brazil - Somavilla, Alexandre; de Oliveira, Marcio Luiz (EntomoBrasilis, 2013)
In this paper we record the occurrence of Clypearia apicipennis (Spinola, 1851), Leipomeles pusilla (Ducke, 1904), Metapolybia nigra Richards, 1978, Parachartergus richardsi Willink, 1951 and Pseudopolybia langi Bequaert, 1944 in Amazonas State for the first time, including distribution notes. Novos Registros de Vespas Sociais (Hymenoptera: Vespidae, Polistinae) no Estado do Amazonas, Brasil Resumo. Nesse trabalho registramos a ocorrência de Clypearia apicipennis (Spinola, 1851), Leipomeles pusilla (Ducke, 1904), Metapolybia nigra Richards, 1978, Parachartergus richardsi Willink, 1951 e Pseudopolybia langi Bequaert, 1944 pela primeira vez no estado do Amazonas e incluímos notas de distribuição.